2020
DOI: 10.1155/2020/8068710
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Characteristics of Type 1 Diabetes Patients during High Mountain Trekking

Abstract: In this study, the aim was to provide observational data from an ascent to the summit of Mount Damavand (5670 meters above sea level (m.a.s.l), Iran) by a group of people with type 1 diabetes (T1DM), with a focus on their physiological characteristics. After a 3-day expedition, 18 T1DM patients, all treated with personal insulin pumps, successfully climbed Mount Damavand. Information was collected on their physiological and dietary behaviors, as well as medical parameters, such as carbohydrate consumption, glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Beta cells, however, are unable to adjust to the long-term demands of peripheral insulin resistance when T2D develops, and the hyperinsulinemia state transforms into a condition of relative insulin insufficiency. As a result, hyperglycemia happens following the consumption of many carbs [16]. Some of the mechanisms involved in beta cell dysfunction and death in T2D are as follows:…”
Section: Discussion Insulin Resistance and Beta Cell Deathmentioning
confidence: 99%
“…Beta cells, however, are unable to adjust to the long-term demands of peripheral insulin resistance when T2D develops, and the hyperinsulinemia state transforms into a condition of relative insulin insufficiency. As a result, hyperglycemia happens following the consumption of many carbs [16]. Some of the mechanisms involved in beta cell dysfunction and death in T2D are as follows:…”
Section: Discussion Insulin Resistance and Beta Cell Deathmentioning
confidence: 99%
“…The metabolic parameters measured with the percentage of HbA1c were worse in patients with depressive-anxiety disorders and with a high level of B-PaidBM [7]. In recently published papers, we have shown that the combination of specific personality traits, social skills, family support, sports traditions, inheritance factors and access to new technologies in the treatment of T1DM under the supervision of a highly qualified specialist diabetolo-gist may result in a unique and inspiring successful success in life, sport and treatment of diabetes [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…There will be overlap with those experienced in other endurance exercise events. Dietary changes, glycaemia and different insulin delivery systems have been explored in extreme events such as high-altitude mountain trekking ( 11 , 12 ), a 1008km bicycle event ( 13 ) and ultramarathon running ( 14 ). The unique and overlapping factors impacting long-distance swimming will be explored in this paper, drawing on published papers, clinical guidelines, and the personal account of an endurance swimmer with type 1 diabetes.…”
Section: Introductionmentioning
confidence: 99%